2018
DOI: 10.1007/s40261-018-0740-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine Treatment on Incident Dementia in Adults with Atrial Fibrillation and Hypothyroidism

Abstract: Background and Objective The possible adverse or positive effects of levothyroxine treatment among patients with atrial fibrillation have been debated. Atrial fibrillation, levothyroxine treatment, and dementia are common among older adults, yet little is known about the effects of levothyroxine on the development of dementia. Methods The study population included all adults ( n = 12,057) aged ≥ 45 years with a diagnosis of atrial fibrillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…22,23 A major strength of our study is the inclusion of two cohorts (DNPR and OPENTHYRO) with validated definitions of both hypothyroidism and dementia but with different ascertainment procedures, thereby limiting some of the shortcomings of other studies. [8][9][10][11]24 In the DNPR cohort, we identified all hypothyroid patients evaluated within the secondary healthcare system in Denmark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 A major strength of our study is the inclusion of two cohorts (DNPR and OPENTHYRO) with validated definitions of both hypothyroidism and dementia but with different ascertainment procedures, thereby limiting some of the shortcomings of other studies. [8][9][10][11]24 In the DNPR cohort, we identified all hypothyroid patients evaluated within the secondary healthcare system in Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this increased burden of comorbidities also includes dementia is currently debated 7 . Some studies indicate an increased risk of Alzheimer's disease (AD), 8,9 and while others found no association to AD, a significantly higher risk of vascular dementia has been found in hypothyroid individuals (VD) 10 . Nonetheless, others failed to show any association between dementia and hypothyroidism 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we only had access to diagnoses of hypothyroidism in the Inpatient Register, while no diagnoses from primary care are included, and we had no possibility to identify patients with levothyroxine treatment without a diagnosis of hypothyroidism. In an earlier, smaller study (n = 12,057) of AF patients in primary care, as much as 35% of the patients, could not be identified with a diagnosis of hypothyroidism [19]. Moreover, AF could not be classified as paroxysmal, persistent or permanent and heart rhythm could not be classified as sinus rhythm or fibrillation rhythm.…”
Section: Discussionmentioning
confidence: 90%
“…However, there are studies challenging this conclusion. In a study of AF patients in Swedish primary care, a lower risk of dementia was found in women with hypothyroidism and levothyroxine treatment, while no such association was found in men and women with levothyroxine treatment but without a diagnosis of hypothyroidism [19]. Besides, in animal models an association between treatment with thyroid hormones and an improved brain function has been shown [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…A recent comprehensive review of the literature based on the current knowledge of the effects of thyroid hormones on brain and their role in Alzheimer's disease suggested that thyroid hormones produce significant neurological effects, act as neuroprotective agents and might be considered as future diagnostic and therapeutic tools for Alzheimer's disease [2]. Women with atrial fibrillation with levothyroxine treatment and hypothyroidism have been reported to have a lower risk of incident dementia than women with atrial fibrillation without levothyroxine treatment and no hypothyroidism [3], supporting a result of comprehensive review [2]. Thyroid hormones may play an important role in the brain function in both early and late life.…”
Section: Hidekatsu Yanaimentioning
confidence: 99%